Review on the protective activity of osthole against the pathogenesis of osteoporosis - Chen, Jincai; Liao, Xiaofei; Gan, Juwen (Frontiers in Pharmacology, 2023)
Osteoporosis (OP), characterized by continuous bone loss and increased fracture risk, has posed a challenge to patients and society. Long-term administration of current pharmacological agents may cause severe side effects. Traditional medicines, acting as alternative agents, show promise in treating OP. Osthole, a natural coumarin derivative separated from Cnidium monnieri (L.) Cusson and Angelica pubescens Maxim.f., exhibits protective effects against the pathological development of OP.Osthole increases osteoblast-related bone formation and decreases osteoclast-related bone resorption, suppressing OP-related fragility fracture. In addition, the metabolites of osthole may exhibit pharmacological effectiveness against OP development. Mechanically, osthole promotes osteogenic differentiation by activating the Wnt/ -catenin and BMP-2/Smad1/5/8 signaling pathways and suppresses RANKL-induced osteoclastogenesis and osteoclast activity. Thus, osthole may become a promising agent to protect against OP development. However, more studies should be performed due to, at least in part, the uncertainty of drug targets. Further pharmacological investigation of osthole in OP treatment might lead to the development of potential drug candidates.